Biosimilar pegfilgrastim may offer affordable treatment options for patients in France: a budget impact analysis on the basis of clinical trial and real-world data. (1st January 2021) - Yang, Jingyan; Liu, Rongzhe; Granghaud, Anna; Zaidi, Omer; Stephens, Jennifer
Abstract: Background: NYVEPRIA, a pegfilgrastim (a long-acting granulocyte colony-stimulating factor [G-CSF]) biosimilar, was recently recommended for marketing authorization in Europe for decreasing the incidence of febrile neutropenia (FN) in patients with non-myeloid malignancies receiving myelosuppressive anti-cancer drugs. The present study aimed to evaluate the financial impact of introducing a new pegfilgrastim biosimilar from a French healthcare system perspective. Methods: An Excel-based budget impact model was developed to estimate the financial impact by introducing a new pegfilgrastim biosimilar (NYVEPRIA) to France over a 5-year time horizon. Comparators included existing long-acting and short-acting G-CSFs. The burden of FN was obtained from existing literature. Costs (2021 Euros) included drug acquisition and administration, estimated based on drug dosage in both clinical trial and real-world settings. Scenario analyses were conducted to examine the robustness of key model assumptions. Results: In a total French population of 67.19 million, 79, 873 patients were estimated to be treated with G-CSFs annually. The annual number of patients to be treated with NYVEPRIA was estimated to be 1593, 3195, 3674, 3782, and 4052 in years 1 to 5, respectively. Using real-world data, NYVEPRIA resulted in total annual cost savings of €8, 620, €868, 498, €868, 498, €814, 102, and €958, 952 over years 1 to 5, respectively, leading to a cumulative 5-year cost savings of €3, 518, 669. Using data from clinical trials, NYVEPRIA resulted in total annual cost savings of €14, 366, €1, 447, 496, €1, 447, 496, €1, 356, 836, and €1, 598, 253 over years 1 to 5, respectively, leading to a cumulative 5-year cost savings of €5, 864, 448. Conclusions: The introduction of a new pegfilgrastim biosimilar (NYVEPRIA) is potentially associated with substantial cost savings for the French healthcare system.